2000
DOI: 10.1002/(sici)1099-0518(20000601)38:11<2013::aid-pola100>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

New polymer syntheses. 102. Aspirin-modified LC polyesters based on PET and 4-hydroxybenzoic acid

Abstract: Four series of liquid‐crystalline copolyesters were prepared by the transesterification of poly(ethylene terephthalate) (PET) with 4‐acetoxybenzoic acid (4‐ABA) or mixtures of 4‐ABA and acetylsalicylic acid (ASA). Two series consisted of 30 mol % PET, and the other two series consisted of 40 mol % PET. The molar ratio of 4‐HBA and ASA was varied in all four series from 0 to 25 mol %. One 30% PET series and one 40% PET series were prepared with the addition of acetic acid, which caused a more perfect randomizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Third, the polymer completely degrades because of the hydrolytically labile anhydride and ester bonds within the backbone. Examples of other salicylate-based polymers are found with low concentrations of salicylate (∼20 wt %) in the backbone or which are simply homopolymers of salicylic acid , (i.e., no linker molecules) such that release of salicylate cannot be readily modified.…”
Section: Introductionmentioning
confidence: 99%
“…Third, the polymer completely degrades because of the hydrolytically labile anhydride and ester bonds within the backbone. Examples of other salicylate-based polymers are found with low concentrations of salicylate (∼20 wt %) in the backbone or which are simply homopolymers of salicylic acid , (i.e., no linker molecules) such that release of salicylate cannot be readily modified.…”
Section: Introductionmentioning
confidence: 99%
“…All copolyesters of this work were prepared with 5% of isosorbide, because all previous studies of isosorbide-containing copolyesters have shown that higher fractions are unfavorable for the formation of a Grandjean texture. , Isosorbide is known 29 to possess a high helix twisting power, and obviously, a high molar fraction of isosorbide generates helices with a pitch which is too small for the interaction with visible light. The substituted hydroquinones were selected as diphenols because the para position of the hydroxy groups favors the formation of LC phases and because substituted hydroquinones have proven in previous studies to favor the formation of noncrystalline cholesteric poly(ester imide)s. In contrast, the incorporation of catechol results in amorphous copoly(ester imide)s as expected from similar studies of catechol countaining LC polyesters . The chemical structure and composition of all polyesters were checked by elemental analyses (see Table ) and by IR and 1 H NMR spectroscopies.…”
Section: Resultsmentioning
confidence: 76%
“…The substituted hydroquinones were selected as diphenols because the para position of the hydroxy groups favors the formation of LC phases and because substituted hydroquinones have proven in previous studies 30 to favor the formation of noncrystalline cholesteric poly-(ester imide)s. In contrast, the incorporation of catechol results in amorphous copoly(ester imide)s as expected from similar studies of catechol countaining LC polyesters. 31 The chemical structure and composition of all polyesters were checked by elemental analyses (see Table 2) and by IR and 1 H NMR spectroscopies. The elemental analyses showed the greatest difference of calculated and experimental values for the C atoms.…”
Section: Resultsmentioning
confidence: 99%
“…In the last few decades, many MC-LCPs and SC-LCPs have been synthesized and investigated [48][49][50][51][52][53][54][55][56][57][58][59][60]. These polymers include: polyesters, polyethers, polyamides, polyurethanes, polysiloxanes, polyamines, polythioether, and polyazomethines.…”
Section: According To the Phasesmentioning
confidence: 99%